An Analysis On Record Politeness of Pragmatic In Tinker Bell And The Great Fairy Rescue Movie - Pipit Aulia; Rani Marliani; Lilis Suryani (IKIP Siliwangi, 2019)
This research is a linguistic study on record politeness of pragmatic in tinker bell and great fairy rescue movie, which aims to know many types of politeness and the most dominant politeness in the film. Researchers use qualitative method and the data are analyzed based on the politeness theory by Brown and Lavinson (1987). The movie lasted 1 hour 25 minutes, including 30 conversation. The result showed that there are four politeness, they are conversation bald on record (16), positive politeness (8), negative politeness (2), and off record (2). In addition the most of dominant politeness is bald on record. It means that the bald on record is an order that is directly when a someone do something in urgent situation